Aktuální pohled na fibromyalgii - Tomš, Jan (Casopis lekaru ceskych, 2012)
Fibromyalgia is a chronic syndrome characterized by dysfunction of pain processing and regulation. Although the definite etiology has not been recognized yet, the key role in the pathogenesis of this syndrome probably plays the central sensitization process with the development of chronic (central) pain and other associated symptoms (fatigue, stiffness, sleep disorders, cognitive and vegetative disturbance). The absence of objective diagnostic tests often results in delayed diagnosis and patient fluctuation among a number of specialists with uncertainty and fear of a serious disease. The treatment is based on the individually adjusted and multidisciplinary approach to the patient, combining pharmacological and non-pharmacological therapy. New drugs introduced to the therapy in the recent years can have positive effect on symptom reduction and improvement of patients quality of life. Key words: fibromyalgia, chronic pain, fatigue, central sensitization.
Keywords: prognóza; Prognosis; Fibromyalgia; Diagnosis, Differential; lidé; Humans; fibromyalgie; diferenciální diagnóza